Proyecto de implementación de una pista de hielo sintético en la ciudad de Guayaquil - Candell Parra, Karen Elizabeth (2010)
Some years ago the Guayaquil entertainment options were limited, and there were only a few cinemas and a few shopping centers that did not offer anything special to the consumer. At present, this sector has grown and now we can see many places of entertainment in Guayaquil who offer their services in modern facilities that provide convenience to its customers. The problem is that the market is saturated with entertainment options in the same subject. The service we provide our project is the practice of synthetic ice skating as a recreational activity and entertainment designed for the enjoyment of young and old, allowing closer so dramatically to the feeling of skating on natural ice, and an air of distraction with a different view of competition. As time passes and we are successful in the city of Guayaquil, we wish to settle in other sectors. Since our vision is to become a center chain synthetic ice skating with a special touch and a refreshing and innovative idea to become an icon of fun in Ecuador. "Dive into the adventure and enjoy the magic of the ice."